Optimizing Group Transfer Catalysis by Copper Complex with Redox-Active Ligand in an Entatic State - Ren, Yufeng; Forté, Jeremy; Cheaib, Khaled; Vanthuyne, Nicolas; Fensterbank, Louis; Vezin, Hervé; Orio, Maylis; Blanchard, Sébastien; Desage-El Murr, Marine (iScience, 2020)
Metalloenzymes use earth-abundant non-noble metals to perform high-fidelity transformations in the biological world. To ensure chemical efficiency, metalloenzymes have acquired evolutionary reactivity-enhancing tools. Among these, the entatic state model states that a strongly distorted geometry induced by ligands around a metal center gives rise to an energized structure called entatic state, strongly improving the reactivity. However, the original definition refers both to the transfer of electrons or chemical groups, whereas the chemical application of this concept in synthetic systems has mostly focused on electron transfer, therefore eluding chemical transformations. Here we report that a highly strained redox-active ligand enables a copper complex to perform catalytic nitrogen- and carbon-group transfer in as fast as 2 min, thus exhibiting a strong increase in reactivity compared with its unstrained analogue. This report combines two reactivity-enhancing features from metalloenzymes, entasis and redox cofactors, applied to group-transfer catalysis. [Display omitted] •We design a catalyst interfacing two reactivity-enhancing tools from metalloenzymes•This work merges redox-active cofactors and entatic state reactivity•The modifications in the coordination sphere lead to enhanced catalytic behavior•These results open perspectives in bioinspired catalysis and group-transfer reactions Inorganic Chemistry; Molecular Inorganic Chemistry; Catalysis